Pengaruh Etos Kerja dan Integritas Terhadap Kinerja Pegawai Negeri Sipil di Lingkungan Organisasi Perangkat Daerah Kota Padang - Mhd. Aski (Journal of Education on Social Science (JESS), 2020)
This study aimed to determine and analyze how much the influence of the work ethic and integrity on the performance of Civil Servants (PNS) within the Regional Government Organizations/Agencies (OPD), Regional Secretariat, Legislator Secretariat, Inspectorate Office, and some SubDistrict offices in Padang City. The method used in this study was associative quantitative. The population of this study was all civil servants within the Regional Government Organizations/Agencies (OPD), Regional Secretariat, Legislator Secretariat, Inspectorate Office, and some SubDistrict offices in Padang City. The sample size in this study used the Bartlett formula and the sample was determined through proportional stratified random sampling. Data in this study were collected through questionnaire with a Likert scale measurement. The data obtained were then analyzed using multiple linear regression. The results of this study showed that the effect of work ethic and integrity variables had significantly influenced on the performance of Civil Servants (PNS) in the Regional Government Organizations/Agencies (OPD), Regional Secretariat, Legislator Secretariat, Inspectorate Office, and some SubDistrict offices in Padang City.